Remodeling of cell wall components mediated by the C4 protein of the geminivirus TYLCSV in tomato - Silvia Rotunno; Camilla Sacco Botto; Laura Miozzi; Marco Catoni; Yiguo Hong; Lorenzo Costamagna; Veronica Volpe; Chiara D’Errico; Andrea Genre; Emanuela Noris (Plant Stress, 2025)
We previously showed that tomato yellow leaf curl Sardinia virus (TYLCSV, Genus Begomovirus, family Geminiviridae) confers enhanced drought tolerance in tomato plants, possibly through the intervention of C4, a small and highly variable viral protein found to be involved in symptoms development, virus movement, RNA silencing suppression, and host defense. We also reported that transgenic tomato plants overexpressing the TYLCSV C4 protein display morphological defects and are tolerant to extreme drought and fungal attack. To define the molecular basis underpinning these phenotypes, a comparative transcriptome analysis was carried out for C4 transgenic and wild-type plants. Gene Ontology and KEGG pathway enrichment analyses highlighted the differential expression of genes mainly related to the metabolism of carbohydrates, fatty acids, phenylpropanoids, and carotenoids. The transcriptional deregulation of key genes involved in the formation of cell wall and cuticle components was confirmed by RT-qPCR. Confocal laser scanning microscopy revealed that the epidermal cells of C4 transgenic leaves have thicker cell walls and cuticles compared to wild-type plants. Moreover, using Raman spectroscopy we confirmed that C4 overexpression leads to higher accumulation of carotenoids and of the major structural cell constituents, such as lignin, cellulose, and pectin. Our findings support the hypothesis that C4 mediates the remodeling and reinforcement of cellular barriers possibly contributing to prime plants against drought stress and fungal attack, deepening the comprehension of the intricate interplay between geminiviruses, plant structure, and responses to abiotic and biotic stresses.